Place Branding in Baden-Württemberg: Wie ein Bundesland High Potentials durch Standortmarketing erreichen kann - Nina Biermann; Irene Mahle; Jens U. Pätzmann (Markenbrand, 2015)
– This article handles the topic "Place Branding" using the example of Baden-Württemberg. Here the place branding measures of the German state Baden-Württemberg are examined, to lead the way in serving the target group "High Potentials" to further development. By complying with the recommendations regarding various offline, online, and university marketing measures, Baden-Württemberg would strengthen its leadership role and would better position itself as an attractive region to live for young leaders. The most important criteria to reach the target group "High Potentials" is to generate awareness for the area as early as possible. It would be optimal to get the leaders of tomorrow enthusiastic about an area already during their studies.
Keywords: 650